Research of cloud disk system construction in campus network - Jun LI; Feng-dan LAO; Ren-ming ZOU (Tongxin xuebao)
According to the significance and demand of cloud disk system in campus network,a solution of combining the miniyun open source project,LVS(Linux virtual server) load balancing,Moosefs distribute file system and MySQL master-slaver replication read/write splitting was proposed to construct high availability cloud disk system.A cloud disk system was built and put into practice based on this solution in China agricultural vnirersity.The application results shows that it meets the demand for cloud disk in campus network with characteristics of low cost,dynamic scalable and high availability.